Environmental regulation in the new global economy : the impact on industry and competitiveness - Jenkins, Rhys. (Cheltenham; Northampton Edward Elgar, 2002)
This book attempts to answer these questions using case studies of three pollution-intensive industries: iron and steel, leather tanning and fertilizers. Based on in-depth interviews with managers and regulators in Western and Eastern Europe, Asia, Africa and Latin America, the book illustrates the variety of responses to the conflicting pressures of globalisation and environmental protection at corporate and industry levels. It also considers the impact which shifting competitive advantage has on the environment in newly industrialized countries and transition economies.
Papers resulting from a conference held in 1999 at the University of East Anglia.
Includes bibliographical references and index.
gau 20/06/14, ijb 09/04/2019
Loans
Keywords: Environmental policy; Environmental policy - economic aspects; Environmental law; Environmental law - compliance costs; Factory and trade waste; Factory and trade waste - environmental aspects; Globalization; Globalization - environmental aspects; Competition, International; Developing countries